Penggunaan Tunjuk Silang pada Arsip Dinamis Aktif Sekretariat Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Wahyuni, Putri; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2014)
This paper describes the cross-reference in National Library and Archives of  West Sumatera. The procedure of storage for cross-reference, and the obstacle that has happened by using the cross-reference in National Library and Archives of West Sumatera. Therefore the institute aware about the problem that has  happened. The theory in this papers related to the archives that have contained meaning, purpose, advantages, and the types of archives. The methods that has used in writing this papers is the field observation and interviews with staff at the Library and Archieves of  West Sumatera. Analyzing the data were analyzed descriptively. Data retrieval is done by using an interview guide in the form of a question, a tool used for doing the interview using (pens, books, as well as camera and a voice recorder). The research object interview with Kasubbid of Repertoire of Services and Expansions of the agency named Mrs. Kiswati, SS. MPA in the National Library and Archieves in West Sumatera. Based on study, we can conclude the folowing: (1). the storage of archieves or document for cross reference has made by two storages area that are in its won box and its own folder. For filling a separate box or boxes of documents stored in filling cabinets, while a separate folder using hanging folders stored in filling cabinets and filling the storage cabinets; (2). The using of cross-reference in the National Library and Archieves of The West Sumatera as a reference or guidelines that has problem with two storage areas. In using of Cross-references depends on the archivists to decide an archieve that has needed the cross-refference or not; (3). Constraints in the use of the cross-reference in The National Library and Archives of  West Sumatera are: the use of cross-reference depends on how the person who do the cross-reference, the lack of human resource as specialized training in conducting cross-reference, other than that, the lack of coordination between the ares in National Library and Archieves in West Sumatera to appoint a cross-reference on archival paper, which in fact shows a cross only for files that have attachments such as photos, maps, blueprints, tapes, and films, as well as a lack of budget or funds to conduct the cross refference. Keywords: filling cabinets; cross-reference